Cystic Lesions of the Pancreas: Clinical and Pathologic Review of Cases in a Five Year Period - Parra-Herran, Carlos E; Garcia, Mónica T; Herrera, Loren; Bejarano, Pablo A (JOP. Journal of the Pancreas, 2010)
Context Cystic lesions of the pancreas represent an important subgroup of pancreatic tumors. The characterization of these lesions has evolved in recent years, and will continue to change according to the increasing number of biopsies and resections performed. Design Pancreatectomy specimens containing cystic lesions collected over a five-year period were reviewed. Main outcome measures Demographic and pathologic features were recorded. Setting Cases were subclassified in diagnostic categories and were grouped according to the nature of the lesion (non-neoplastic vs. neoplastic). Results Of 361 pancreatic lesions, 97 cysts corresponding to 95 patients were studied. The patients’ mean age was 60 years. Sixty two cysts (63.9%) occurred in women. Among the 97 cysts, five (5.2%) were non-neoplastic and 92 (94.8%) were neoplastic (59.8% benign, 17.5% borderline, 17.5% malignant). Intraductal papillary mucinous neoplasm was the most common diagnosis (n=51; 52.6%) followed by serous cystic neoplasm (n=20; 20.6%) and mucinous cystic neoplasm (n=13; 13.4%). Frequency of female gender was higher and age was lower in the borderline lesions (P=0.001 and P=0.002, respectively). Tumor size was significantly lower in benign neoplastic lesions (P=0.045). Incidental identification was more frequent in benign lesions (P=0.028), whereas malignant lesions were more frequently symptomatic (P=0.001). Conclusion Cystic lesions are found in 20.6% of all pancreatectomy specimens. Among this heterogeneous group, benign neoplasms predominate, particularly those with mucinous lining. Age at presentation, gender, location and tumor size are highly variable, with the exception of solid pseudopapillary tumor. Clinical presentation, diagnostic imaging and laboratory data should be consistently reported to improve the therapeutic approach. Image: Cystic lesions of the pancreas.